Seasonal patterns of atmospheric trace element concentrations in Upstate New York, USA - (:unkn) unknown (KLUWER ACADEMIC PUBL, 2004)
Ambient aerosol and gas phase mercury samples at five, and wet deposition samples at two rural sites were collected for two years (1991-1993) in New York State, USA. Element concentrations of more than 2000 samples were determined by instrumental neutron activation analysis (INAA) to explain probable source types and source regions of observed trace elements. Concentrations for many of the elements displayed distinct seasonal patterns. This, among other reasons may be due to changes in the prevailing winds over the region and seasonal changes in some of the source strengths.
Keywords: FINE; STATE; SIGNATURES; AEROSOLS; MERCURY